Relationship between Skill Requirements and Challenges of Internet of Things (IoT) Implementation in Construction Project - Lee , Chin Ying; Kasim, Narimah; Zainal, Rozlin; Abd Rahim, Mohd Hilmi Izwan (Research in Management of Technology and Business, 2024)
The research investigates the crucial relationship between skill requirements and challenges of Internet of Things (IoT) implementation in construction projects. Recognizing the transformative potential of IoT in enhancing project management and efficiency, the study aims to address obstacles that impede its successful integration. It delves into the relationship between skill requirements and challenges of Internet of Things (IoT) implementation in construction projects, shedding light on various aspects of its adoption. The objective is to identify specific skill requirements, examine challenges faced during IoT implementation, and analyze the correlation between skill requirements and challenges in construction projects. Utilizing a quantitative approach, the study gathered primary data through surveys distributed to G7 contractors in Johor, Malaysia. Moreover, secondary data from existing literature was reviewed to provide comprehensive insights. The SPSS software was employed for meticulous data analysis, facilitating the extraction of meaningful statistics such as frequency distributions. This analysis aids in understanding the relationship between IoT skills and challenges in construction projects. This research significantly contributes to the construction industry by providing clarity on the skill requirements necessary for successful IoT adoption. This enables businesses to effectively train their staff and enhance project outcomes. The study adds to the body of knowledge by evaluating precise skills required and offering insights into challenges hindering IoT integration. In conclusion, the study underscores the essential nature of IoT skills for successful implementation in construction projects, emphasizing the need for skill development to overcome challenges and contribute to the overall advancement of the industry.